An Aerospace Business Case on Additive Layer Manufacturing Technologies in Aerospace and Defense Supply Chain - Kemsaram, Narsimlu; Maley, Kishore Kumar (ExcelingTech, 2019)
This paper provides an overview of activity-based costing for the end-to-end additive layer manufacturing or 3D printing process. It explains to understand the cost drivers associated with additive layer manufacturing process. Using activity-based costing, we can breakdown the cost drivers and understand the cost levers associated with additive layer manufacturing process. This can help us in finding the innovative ways to enhance the additive layer manufacturing process operation's efficiency. It also helps to assess the machine true value. We have considered an aircraft bracket manufacturing using the direct metal laser sintering process as a business case for our market analysis on 3D printing supply chain. The 3D printed components associated cost can be divided into various steps such as component design, component production, component post-processing, and component qualification. Each step in the 3D printing process performs at one place or across a supply chain based on the various internal and external suppliers. Also, there are overhead costs associated with each step of this 3D printing process. This paper explains the cost involved in the component design and its relevance to supply chain. It explains the cost involves in the component production such as materials cost, machine setup cost, machine run time cost, and final build plate removal cost. Its also explains the cost involves in the post-processing such as heat-treating cost, machining cost, and surface finish cost. The component process cost is required to qualify based on its end use. The component qualification cost is required to add significantly to the component overall cost including the labour cost and computer tomography scan cost. The overhead cost is depending on the individual operation and it assigns these costs appropriately. It computes the activity-based costing for an aerospace component and concludes with analysis to make a convincible business case for the use of innovative technology and enable to identify the cost drivers and levers, so it can drive business with more efficiently.Keywords Activity Based Costing, Additive Layer Manufacturing, Aerospace and Defense, Aerospace Business Case, 3D Printing, Supply Chain Management